The Structure of Prison in Contemporary Narrative Discourse: The Novel “From Skhirat to Tazmamart: A Round-Trip Ticket to Hell” as a Model - lakehal, abdelkader; benyahia, abbas (El Omda in Linguistics and Discourse Analysis, 2023)
Prison is considered one of the most important themes in modern Arabic narrative discourse, as can be seen in the autobiographical narrative “From Skhirat to Tazmamart: A Round-Trip Ticket to Hell” by a Moroccan prisoner who lived through a highly significant and dangerous historical period in his country’s and region’s history. This period witnessed major social, political, and regional transformations that deeply influenced the Moroccan individual’s perception of the homeland, through the events he experienced and the figures he encountered. This narrative has produced new semantic dimensions and structures of prison and of narrative space in general, which we will attempt to elucidate through the corpus under study. This text is considered one of the most important modern prison writings, addressing the theme of prison as a space rich in multiple meanings and structural configurations.